An Alternative to Mother's Own Milk: Maternal Awareness of Donor Human Milk and Milk Banks. (February 2021) - Ellsworth, Lindsay; Sturza, Julie; Stanley, Kate
Background: The use of donor human milk is rising. Maternal awareness of donor human milk use, milk donation, and milk banks has not been well described in the United States. Research Aims: To explore maternal experience, knowledge, and attitudes regarding donor human milk use and milk donation. We also assessed counseling by medical providers about donor human milk use and donation. Methods: A cross-sectional prospective survey design was used in this study. We anonymously surveyed mothers ( N = 73) attending the 1 to 2-week well newborn appointment. Analyses were completed using one-way ANOVA and logistic regression. Results: Participants' infants primarily received their own mother's milk (87%, n = 61). No infants received donor human milk, but 4% ( n = 3) of participants donated milk. The majority of participants had positive responses to attitudinal statements about donor milk. When presented with a hypothetical scenario, participants chose formula (89%, n = 59) over donor human milk (11%, n = 7) for their infant. Moreover, if donor human milk was the only option available, they chose donor human milk from a relative or friend (60%, n = 40) over a milk bank (40%, n = 26). Medical providers had discussed donor human milk use or donation with 4% ( n = 3) of participants. Conclusions: The majority of participants previously had minimal experience using donor human milk and limited knowledge regarding donor human milk and milk banks. According to participants, medical providers did not routinely discuss milk donation and the role of donor human milk with families.